YILDIRIM, İsmail; Milli Mücadele’nin Başlangıcında Eskişehir (22 Ocak 1919-20 Mart 1920), Eskişehir Büyükşehir Belediyesi Yayını, Uğur Ofset AŞ.,Eskişehir, 1998, VIII+94 Sayfa, ISBN:975-94323-0-7 - Haykır, Handan (My University, 2014)
-
Keywords: Tarih